Assessment Nurses role in Reducing Hospital Stay of Patients with Respiratory Diseases in some Basrah Teaching Hospitals - Alsaad, Anmar Jabbar; Ali Suanid Alethar; Maher Abdul Ameer Atiyah (Indonesian Journal on Health Science and Medicine, 2025)
Prolonged hospital stay is a major concern in healthcare systems, as it increases the risk of hospital-acquired infections, elevates treatment costs, and reduces bed availability. Nurses play a central role in patient care, and their interventions can significantly influence recovery outcomes and hospitalization duration. In surgical wards, particularly among patients undergoing abdominal surgeries, the quality of nursing care and adherence to postoperative protocols are essential determinants of hospital stay length. While the impact of medical and surgical interventions has been widely studied, limited research has evaluated the direct role of nurses in reducing hospital stay through evidence-based practices. This study aimed to assess the role of nurses in reducing the length of hospital stay among patients undergoing abdominal surgery at Al-Najaf Al-Ashraf Teaching Hospital. A cross-sectional study of 60 nurses revealed that 68.3% demonstrated good knowledge and practice in postoperative care, including infection prevention, pain management, wound care, and patient education. The study confirmed a positive relationship between effective nursing interventions and reduced hospital stay. Unlike previous studies focusing on physician-led interventions, this research highlights nursing contributions as a critical factor in optimizing patient outcomes. The findings emphasize the importance of continuous nursing education, protocol adherence, and supportive hospital policies to enhance recovery rates, reduce complications, and minimize hospitalization duration. Highlights: Nurses play a vital role in reducing hospital stay duration for patients with hematological malignancies. Effective nursing care enhances treatment adherence and improves overall patient outcomes. Strengthening nurses’ skills and involvement in care can significantly optimize hospitalization periods.